Transformation of (+/-)-lavandulol and (+/-)-tetrahydrolavandulol by a fungal strain Rhizopus oryzae - Daramwar, Pankaj P.; Rincy, Raju; Niloferjahan, Siddiqui; Krithika, Ramakrishnan; Gulati, Arvind; Yadav, Amit; Sharma, Rakesh; Thulasiram, Hirekodathakallu V. (Bioresource Technology, 2012)
Biotransformation of an irregular monoterpene alcohol, (+/-)-lavandulol [(+/-)-5-methyl-2-(1-methylethenyl)-4-hexen-1-ol] (I) and its tetrahydro derivative, (+/-)-tetrahydrolavandulol [(+/-)-2-isopropyl-5-methylhexan-1-ol] (II) were studied using a soil isolated fungal strain Rhizopus oryzae. Five metabolites, 2-((3,3-dimethyloxiran-2-yl)methyl)-3-methylbut-3-en-1-ol (Ia), 2-methyl-5-(prop-1-en-2-yl)hex-2ene-1,6-diol (Ib), 2-methyl-5-(prop-1-en-2-yl)hexane-1,6-diol (Ic), 2-(3-methylbut-2-enyl)-3-methylenebutane-1,4-diol (Id), 5-methyl-2-(2-methyloxiran-2-yl)hex-4-en-1-01 (Ie) have been isolated from the fermentation medium and characterized with lavandulol as a substrate. When tetrahydrolavandulol used as a substrate, two metabolites 2-isopropyl-5-methylhexane-1,5-diol (IIa) and 2-isopentyl-3-methylbutane-1,3-diol (lib) have been isolated from the fermentation medium. Biotransformation studies with R. oryzae clearly indicate that the organism initiates the transformation either by hydroxylation at allylic methyl groups or epoxidation of double bond. GC and GCMS analyses indicated that both (R)and (S)-enantiomers of I and II have been transformed into corresponding hydroxylated or epoxy derivatives, when racemic I and II were used as substrates. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biotransformation; Fungus; Lavandulol; Rhizopus oryzae; Tetrahydrolavandulol

Biocatalyst mediated production of 6 beta,11 alpha-dihydroxy derivatives of 4-ene-3-one steroids - Kolet, Swati P.; Niloferjahan, Siddiqui; Haldar, Saikat; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (Steroids, 2013)
Biotransformation of steroids with 4-ene-3-one functionality such as progesterone (I), testosterone (II), 17 alpha-methyltestosterone (III), 4-androstene-3,17-dione (IV) and 19-nortestosterone (V) were studied by using a fungal system belonging to the genera of Mucor (M881). The fungal system efficiently and quantitatively converted these steroids in regio- and stereo-selective manner into corresponding 6 beta,11 alpha-dihydroxy compounds. Time course experiments suggested that the transformation was initiated by hydroxylation at 6 beta- or 11 alpha-(10 beta-hydroxy in case of V) to form monohydroxy derivatives which upon prolonged incubation were converted into corresponding 613,11oc-dihydroxy derivatives. The fermentation studies carried out using 5 L table-top fermentor with substrates (I and II) clearly indicates that 6 beta,11 alpha-dihydroxy derivatives of steroids with 4-ene-3-one functionality can be produced in large scale by using M881. (C) 2013 Elsevier Ltd.
Keywords: 4-Ene-3-one steroids; Biotransformation; Mucor sp.

Mucor hiemalis mediated 14 alpha-hydroxylation on steroids: In vivo and in vitro investigations of 14 alpha-hydroxylase activity - Kolet, Swati P.; Haldar, Saikat; Niloferjahan, Siddiqui; Thulasiram, Hirekodathakallu V. (Steroids, 2014)
Transformation of testosterone and progesterone into synthetically challenging 14 alpha-hydroxy derivatives was achieved by using fungal strain Mucor hiemalis. Prolonged incubation led to the formation of corresponding 6 beta/7 alpha,14 alpha-dihydroxy metabolites. The position and stereochemistry of newly introduced hydroxyl group was determined by detailed spectroscopic analyses. The time course experiment indicated that fungal strain initiated transformation by hydroxylation at 14 alpha-position followed by at 6 beta- or 7 alpha-positions. Studies using cell-free extracts suggest that the 14 alpha-hydroxylase activity is NADPH dependent and belongs to the cytochrome P450 family. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: 14 alpha-Hydroxylase; Biotransformation; Mucor hiemalis; Progesterone; Testosterone